2009
DOI: 10.1021/jf8032254
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Preparing Phenolic Extracts from Olive Cake for Potential Application as Food Antioxidants

Abstract: Olive cake, the most important byproduct of olive oil extraction by the two-phase centrifugation system, was used to obtain phenolic extracts. The extracts were obtained using the two constituents of this waste, vegetative water and solid residue, to maximize the extraction of all phenolic compounds. Different extraction procedures were studied, a simple and rapid extraction procedure being developed from the solid residue using an accelerated solvent extractor (ASE). Afterward, the phenolic extracts were frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 25 publications
3
93
0
2
Order By: Relevance
“…food and cosmetic) or animal feed, but also could contribute to minimize the environmental impacts of this agro-industrial waste. Olive cake was used also to obtain phenolic extracts from its vegetative water and solid residue, to maximize the extraction of all phenolic compounds (Suárez et al, 2009). The authors studied different extraction procedures, a simple and a rapid one, and they found that the phenolic extract obtained by accelerated solvent extraction from the solid residue of olive cake could be proposed as a simple and rapid extraction procedure as an alternative to solid-liquid extraction.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…food and cosmetic) or animal feed, but also could contribute to minimize the environmental impacts of this agro-industrial waste. Olive cake was used also to obtain phenolic extracts from its vegetative water and solid residue, to maximize the extraction of all phenolic compounds (Suárez et al, 2009). The authors studied different extraction procedures, a simple and a rapid one, and they found that the phenolic extract obtained by accelerated solvent extraction from the solid residue of olive cake could be proposed as a simple and rapid extraction procedure as an alternative to solid-liquid extraction.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The concentration of total phenol content ranged from 13 to 22 % depending on the geographical area. They were characterized by their highest antioxidant activity, especially hydroxytyrosol, and some other biological effects such as antimicrobial and anti-inflammatory activities (Allouche et al, 2004;De Marco et al, 2007;Capasso et al, 2002;Suarez et al, 2009;Visioli et al, 2002).…”
Section: Identification Of Phenolic Compounds Extracted From Omwwmentioning
confidence: 99%
“…Different letters mean significant differences (P < 0.05) (Student test). (Dermeche et al, 2013;Obied et al, 2005;Suarez et al, 2009;Obied et al, 2007) a The Results are expressed as percentage of total phenols in OMMW extracts. b Mass charge value.…”
Section: Ft-mir Infrared Spectra Analysismentioning
confidence: 99%
See 2 more Smart Citations